Isotoxic high-dose stereotactic body radiotherapy integrated in a total multimodal neoadjuvant strategy for the treatment of localized pancreatic ductal adenocarcinoma. (October 2021) - Bouchart, Christelle; Engelholm, Jean-Luc; Closset, Jean; Navez, Julie; Loi, Patrizia; Gökburun, Yeter; De Grez, Thierry; Mans, Laura; Hendlisz, Alain; Bali, Maria Antonietta; Eisendrath, Pierre; Van Gestel, Dirk; et al.
Background: Our aim was to evaluate the feasibility and safety of isotoxic high-dose (iHD) stereotactic body radiation therapy (SBRT) in a total neoadjuvant sequence for the treatment of localized pancreatic adenocarcinoma. Materials and methods: Biopsy-proven borderline resectable/locally advanced pancreatic cancer (BR/LAPC) patients were included in this observational prospective analysis from August 2017 to April 2020 without excluding tumours showing a radiological direct gastrointestinal (GI) invasion. An induction chemotherapy by modified fluorouracil, irinotecan and oxaliplatin was performed for a median of six cycles. In case of non-progression, an isotoxic high-dose stereotactic body radiotherapy (iHD-SBRT) was delivered in 5 fractions followed by a surgical exploration. The primary endpoint was acute/late gastrointestinal grade ⩾3 toxicity. Secondary endpoints were overall survival (OS), progression-free survival (PFS) and local control (LC). Results: A total of 39 consecutive patients (21 BR and 18 LAPC) were included: 34 patients (87.2%, 18 BR and 16 LAPC) completed the planned neoadjuvant sequence. After iHD-SBRT, 19 patients [55.9% overall, 13/18 BR (72.2%) and 6/16 LAPC (37.5%)] underwent an oncological resection among the 25 patients surgically explored (73.5%). The median follow up was 18.2 months. The rates of acute and late GI grade 3 toxicity were, respectively, 2.9% and 4.2%. The median OS and PFS from diagnosis were, respectively, 24.5 and 15.6 months. The resected patients had improved median OS and PFS in comparison with the non-resected patients (OS: 32.3 versus 18.2 months, p  = 0.02; PFS: 24.1 versus 7.1 months, p  < 0.001). There was no survival difference between the BR and LAPC patients. The 1-year LC from SBRT was 74.1% and the median locoregional PFS was not reached for both BR and LAPC patients. Conclusions: iHD-SBRT displays an excellent toxicity profile, also for potentially high-risk patients with radiological direct GI invasion at diagnosis and can be easily integrated in a total neoadjuvant strategy. The oncological outcomes are promising and emphasise the need for further exploration of iHD-SBRT in phase II/III trials.